Curfew as a Measure of the Legal Regime of Martial Law and its Impact on the Administrative and Legal Status of Citizens During Martial Law - Korentsov, Oleksandr (Problems of legality, 2025)
The relevance of the present study is conditioned by the fact that since the onset of the full-scale invasion of the Russian Federation’s armed forces into Ukraine, a curfew has been continuously in force for more than three and a half years, yet to date, there has been no comprehensive scholarly inquiry into this particular measure of the legal regime of martial law. In particular, its genesis, the grounds for its introduction under contemporary conditions—when the nature of war is fundamentally different from that of the Second World War, considering modern technological advancements—remain insufficiently explored. The article undertakes an analysis of the provisions of the Law of Ukraine No. 389-VIIIOn the Legal Regime of Martial Law (Law No. 389-VIII), which regulate measures under martial law, specifically the curfew, and which significantly affect the administrative and legal status of citizens during its enforcement. The purpose of the article is to investigate the expediency and justification of the introduction and implementation of a curfew across the entire territory of Ukraine, as well as in its individual regions, under conditions of martial law. Particular attention is paid to its application in circumstances of relative stabilization in combat zones and during the transformation of the full-scale armed aggression of the Russian Federation into a protracted war. The study examines the grounds and conditions under which a curfew is imposed during the enforcement of martial law, as well as the consequences of its application for the exercise of citizens’ rights and freedoms. A reasoned position is articulated regarding the inadmissibility of subjecting individuals to administrative liability for violating curfew regulations (as proposed by members of the Verkhovna Rada through draft legislation), given that the inalienable right to life, according to Article 27 of the Constitution of Ukraine, belongs exclusively to the individual. Therefore, even when an individual neglects their own safety, such conduct cannot constitute grounds for administrative liability. It is emphasized that the imposition of a curfew must pursue a legitimate aim, be both substantiated and temporary, and that once the situation in combat zones stabilizes, this measure of the martial law regime cannot be applied indiscriminately throughout the entire territory of the state. Otherwise, it results in unjustified restrictions on the rights and freedoms of all citizens. It is argued that curfews should be enforced only in cities and settlements located within combat zones, specifically within a fifty-kilometer radius of the line of military confrontation and along the border with the Russian Federation. The article concludes that Law No. 389-VIII and subordinate normative legal acts require substantial amendments, particularly with respect to the grounds for declaring martial law, as well as the introduction, implementation, and cancellation of its measures, including curfews.